PERAN KEPUASAN MEMEDIASI PENGARUH HEDONIC SHOPPING VALUE TERHADAP LOYALITAS PELANGGAN GERAI KOPI - Dewi Sukma, Md Tiara; Sri Suprapti, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
Coffee shop business prospects arise from the occurrence of customers frequent coffee shops. In Denpasar, Starbucks is a well-known coffee establishment with a large following. Customers return to Starbucks locations in Denpasar because they enjoy their shopping experience there. This study's primary goal is to examine and clarify the connection between hedonic shopping value, customer loyalty and satisfaction as a mediator. One hundred thirty people filled out the survey. After the data was collected using questionnaires, the hypotheses were evaluated with the use of the Sobel Test and Path Analysis. The results of analysis indicate that 1) hedonic shopping value has a positive and significant effect on customer loyalty, 2) hedonic shopping value has a positive and significant effect on satisfaction, 3) satisfaction has a positive and significant effect on customer loyalty, 4) satisfaction mediates the effect of hedonic shopping value on customer loyalty. This research that can be used as a reference regarding the relationship between hedonic shopping value, satisfaction, and customer loyalty, and can be used by Starbucks management to consider hedonic shopping value and satisfaction in order to enhance customer loyalty.